Comparative analysis of biomass and soil characteristics of teak (Tectona grandis Linn. F) plantations and natural mixed forests in Bara District, Nepal - Dhamala, Jyoti; Deshar, Rashila (Nepal Journal of Environmental Science, 2025)
Rapidly expanding teak plantations are often considered ecologically inferior to natural forests because they deplete key soil nutrients, which can reduce long-term biomass production and ecosystem health. This study compares the biomass and soil characteristics of teak planted forests (TPF) and natural mixed forests (NMF) in the lowland of Nepal to fill a research gap in the region. A systematic sampling of 15 plots (20 x 20 m2 each) in each forest was conducted to assess trees, saplings, seedlings, and soil properties. The study found that while ten species in the NMF had good regeneration, the high density of teak saplings in the TPF limited regeneration to only one, restricting the growth of other species. Despite these differences in species composition, both forests had a similar total biomass. Soil nutrient properties were significantly lower in the TPF than in the NMF, which received greater nutrient input from annual litterfall and understory growth. However, the lower disturbances in the TPF might have led to comparable levels of organic matter, nitrogen, soil moisture, and sand percentage to NMF. In the TPF, biomass was positively linked to soil pH and nitrogen, while in the NMF, it was related to organic matter, sand, nitrogen, potassium, and canopy cover. The CCA analysis also showed that teak thrived in sand-rich soil with high organic matter, while other species from the study area are found in nutrient-rich conditions. This could be the reason that the NMF had high tree species diversity compared to TPF. This difference may explain the higher tree species diversity observed in the NMF compared to the TPF. The study concludes that while teak monocultures are established primarily for their known economic viability, mixed-species plantations are nevertheless a preferable alternative for achieving a better balance between economic interests and essential environmental integrity.